The role of mood states in cyberbullying and cybervictimization behaviors in adolescents. (June 2021) - De Pasquale, Concetta; Martinelli, Valentina; Sciacca, Federica; Mazzone, Michela; Chiappedi, Matteo; Dinaro, Carmela; Hichy, Zira
Highlights: Cyberbullying represents a public health problem with serious implications for adolescents' mental health Male gender and older age (>15 years) are discriminating factors for both Cybervictimization and Cyberbullying behaviors Mood states are specific predictors of high risk of cyberbullying and cybervictimization behavior Abstract: Cyberbullying is an intentional aggressive behavior repeatedly perpetrated by a single person or a group against a peer who can not easily defend, characterized by the use of electronic forms of contact. This phenomenon is a public health concern with serious implications for adolescents' mental health. We aimed to investigate the role of gender, age, and subjective self perceived mood states in cyberbullying and victimization (being a victim of cyberbullying) behaviors. A total of 554 adolescents (293 males and 261 females, age 15.27; SD = 2.21) completed the Florence Cyber-Bullying Cyber-Victimization Scales (FCBVSs) and the Profile of Mood States (POMS). Older age and male gender were associated to both cyberbullying and victimization.The aggressiveness/anger (A) and confusion/bewilderment (C) factors measured by the POMS were predictors of all types of cyberbulliyng and cybervictimization behaviors; the tension/anxiety (T) factor was a predictor of all cyberbullying behaviors and of the FCBVSs impersonification subscale of cybervictimization. Subjective specific mood states may contribute to both cyberbulliyng and victimization behaviors, suggesting the potential benefit of preventive strategies addressing the recognition and management of mood states in adolescents.